The Westernness of Phrygian Culture - Vassileva, Maya (Ancient Near Eastern studies, 2024)
The present work is focused on the western elements in Phrygian culture, which were the background on which the unique Phrygian polity, as we see at Gordion, was built up. They were of Balkan, Aegean, and western Anatolian origin, on which Anatolian and Near Eastern influences were overlaid. Phrygia differed in many aspects from its Anatolian and Neo-Hittite neighbours, with which it interacted. The differences discussed here are discerned in architecture, script and language, and cult. Attention is paid to the possible asynchronous Thracian – Phrygian parallels in the sphere of alphabet, language, and cult. The new chronology of Gordion inevitably poses the question of the adoption and adaptation of the Greek alphabet, as well as of the borrowing of the Mycenaean titles of Midas, which are here briefly discussed. We still need more archaeological and epigraphic data in order to properly define the nature of the Phrygian polity.